Dose-dependent effects of peroxisome proliferator-activated receptors β/δ agonist on systemic inflammation after haemorrhagic shock. (March 2018) - Yin, Luxu; Busch, Daniel; Qiao, Zhi; van Griensven, Martijn; Teuben, Michel; Hildebrand, Frank; Pape, Hans-Christoph; Pfeifer, Roman
Highlights: High dosage of GW0742 enhanced the plasma pro-inflammatory cytokines levels. Low-dose treatment of GW0742 induced a downtrend of inflammation cytokine levels. GW0742 treatment has no effect on the remote organ neutrophil infiltration. Abstract: Introduction: PPARβ/δ agonists are known to modulate the systemic inflammatory response after sepsis. In this study, inflammation modulation effects of PPARβ/δ are investigated using the selective PPARβ/δ agonist (GW0742) in a model of haemorrhagic shock (HS)-induced sterile systemic inflammation. Methods: Blood pressure-controlled (35 ± 5 mmHg) HS was performed in C57/BL6 mice for 90 min. Low-dose GW0742 (0.03 mg/kg/BW) and high-dose GW0742 (0.3 mg/kg/BW) were then administered at the beginning of resuscitation. Mice were sacrificed 6 h after induction of HS. Plasma levels of IL-6, IL-1β, IL-10, TNFα, KC, MCP-1, and GM-CSF were determined by ELISA. Myeloperoxidase (MPO) activity in pulmonary and liver tissues was analysed with standardised MPO kits. Results: In mice treated with high-dose GW0742, plasma levels of IL-6, IL-1β, and MCP-1 were significantly increased compared to the control group mice. When compared to mice treated with low-dose GW0742 plasma levels of IL-6, IL-1β, GM-CSF, KC, and MCP-1 were significantly elevated in high-dose-treated mice. Low-dose GW0742 treatment was associated with a non-significant downtrend of inflammatory factors in mice with HS. No significant changes of MPO activity in lung and liver were observed between the control group and the GW0742 treatment groups. Conclusion: This study identified dose-dependent effects of GW0742 on systemic inflammation after HS. While high-dose GW0742 substantially enhanced the systemic inflammatory response, low-dose GW0742 led to a downtrend of pro-inflammation cytokine expression. The exact mechanisms are yet unknown and need to be assessed in further studies.